One of us is lying - McManus, Karen M. (Delacorte Press, 2017)
Smart Bronwyn, beautiful Addy, drug-dealer Nate, athlete Cooper, and class outcast Simon--creator of the notorious school gossip app--all walk into Bayview High on a Monday afternoon for detention. The four other students know that Simon plans on publishing juicy gossip about all of them on Tuesday. Before Monday detention ends, Simon is dead, and the others are lying about who killed him.